FAKTOR PENDUKUNG DAN PENGHAMBAT KEPATUHAN PENGGUNAAN OBAT: STUDI KUALITATIF PADA ANAK DENGAN HIV-AIDS DI D.I. YOGYAKARTA - , TINTANI BUNGA R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Children with HIV-AIDS should take antiretroviral drugs for the rest of his life so that adherence to take the medication will affect the quality of life. The purpose of the study is to determine the factors supporting and inhibiting the adherence of children with HIV-AIDS in antiretroviral consumption. The research is using a qualitative study with in-depth interviews to HIV-AIDS children in Victory Plus NGO. Respondents in this study are children under the age of 12 years. However, because of the children treatment decision is still held by the parents, then the interviews are conducted to parentâs respondents. The technique sampling is using purposive sampling. Data analysis that used is theories of health behavior, which is the Health Belief Model (HBM). The results of this study are the factors supporting and inhibiting adherence of antiretroviral drug consumption in children. Supporting factor is the perceived severity of disease, the perceived susceptibility of opportunistic infection, the children knowledge of the importance of taking medication, the improvement condition of children, the lifelong commitment of parents to give children medication and support, information, and reminders from family and Victory Plus NGO. Inhibiting factor is the difficulty of cutting drug according to the doses, the boredom of children, the incitement from the environment, the complicated bureaucracy to get the drugs, and the lack of parental knowledge. Supporting and inhibiting factors in HIV-AIDS children to consume drugs are highly dependent on the role of parents because children can not make their own complete decisions yet.